The Correlation between Students' Motivation and Reading Comprehension at The Second Semester Students at English Language Education at University of Batanghari - Rita Sari (JELT: Journal of English Language Teaching, 2020)
The purpose of this research is want to know is correlation between students’ motivation and reading comprhension students at the second semester at English language education at University of Batanghari. The research is using is quatitative research with a Descriptive, which the data that get is quantitative data and the data is explained as describe. The population of this research is the at second semester students at English Language Education at Univesity of Batanghari and the were 30 respondents were as the sample. The data was  get from the students’ motivation quesionnaires and reading comprehension. the test. After analyzed and calculate the data, it was found that mean of students’ motivation questionnaires was 63% (19) the categorized was in high score, and 37% (11) the categorized was in score low. 0% none was in categorized very high and very low. And the range score of the reading comprehension was 30. The maximum score was 70 and the low score was 40. Meanwhile the sum 1720. The result showed that 87% (26) the categorized good, and 13% (4) the categorized poor. 0% none of the had very good and very poor reading comprehension. It was found the result of the correlation between students' motivation and reading comprehension  is  0.71 is higher that the level of correlation probability which score sig. 0.00. The result indicated that the  is rejected and the is accepted which means that there was a correlation between students’ motivation and reading comprehension at the second semester students at English Language Education at University of Batanghari.Keywords : Students’ Motivation, Reading, Reading Comprehension.